Economic Geology Models 5. Specialty, Critical, Battery, Magnet and Photovoltaic Materials: Market Facts, Projections and Implications for Exploration and Development - Simandl, Laura; Simandl, George J.; Paradis, Suzanne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2021)
Many exploration companies are now focusing on specialty materials that are associated with so-called ‘green technology’. These include ‘battery materials’, ‘magnet materials’ and ‘photovoltaic materials’, and many such commodities are also broadly labelled as ‘critical materials’ because they are seen as vital for industrial development, societal needs or national security. The definitions used for such materials are not always consistent among jurisdictions or across industry, and this paper attempts to clarify the criteria and address some common misconceptions. The distinction between major minerals (e.g. base metals) and ‘specialty materials’ (i.e. those mined or produced in much smaller amounts) is particularly important.The markets for many specialty materials are growing faster than those for traditional ferrous, precious and base metals and they are often portrayed as excellent long-term investment opportunities. However, the small market bases for specialty materials and considerable uncertainty around growth projections (especially related to material substitutions and rapid technological change) need to be taken into consideration for objective assessment of the development potential of any proposed project, establishment of new supply chains by major corporations, and responsible decision-making (mineral policy) by government. In the short-term, projects aimed at specialty materials (materials with a small market base) cannot benefit from economy of scale, and their development hinges on commercially proven metallurgical processes, unless they are supported by governments or end-users.Several specialty metals (e.g. germanium, indium, cadmium, and cobalt) are commonly obtained as by-product of base metal extraction. In such cases, systematic testing of base metal ores for their specialty metal content may justify the addition of relevant recovery circuits to existing smelters. If positive results are obtained, the need for targeting new sources of such specialty metals as primary exploration targets may be reduced or eliminated.Where market conditions permit and concerns about the future availability of materials seem reliable, grass-roots exploration for specialty materials is warranted, and pre-competitive government involvement may be justified to promote such development efforts.